A case of neurofibromatosis type 1 with clival chordoma - Suresh, Thejus; Bhatia, Simran; Hegde, Sindhu S.; Menon, Girish; Karanth, Shubhada (International Journal of Research in Medical Sciences, 2024)
Neurofibromatosis type-1 is an autosomal dominant tumour syndrome with a high clinical susceptibility to malignancies, especially nervous system malignancies. Here, we reported a case of neurofibromatosis type-1 in a male in his 50s, who presented with generalised weakness, headache associated with ear pain, a feeling of heaviness of the head, and giddiness for a duration of 1 week. On examination, he had axillary freckling and multiple neurofibromas over his body. Nystagmus and dysdiadokokinesia were present. MRI brain revealed an enhancing lesion in the sphenoid and clivus, extending into the sellar and supra-sellar region. The possibility of pituitary adenoma and clival chordoma were considered. He was referred to Neurosurgery and underwent Trans-nasal Trans-sphenoidal near-total resection of the tumour. Biopsy of the lesion was indicative of conventional clival chordoma, which is rarely reported with NF-1. The post-operative period was uneventful and the patient is planned for regular follow-up to detect recurrence.